2003
DOI: 10.3171/spi.2003.98.1.0014
|View full text |Cite
|
Sign up to set email alerts
|

Kryorhizotomy: an alternative technique for lumbar medial branch rhizotomy in lumbar facet syndrome

Abstract: Object. The authors conducted a prospective study to investigate the efficacy of kryorhizotomy, an alternative procedure for lumbar medial branch neurotomy, in the treatment of lumbar facet syndrome (LFS). Methods. Fifty patients with chronic low-back pain, in whom pain was relieved by controlled diagnostic medial branch blocks of the lumbar zygapophyseal (facet) joints, underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…Another study [92] demonstrated that of the 50 patients who underwent cryoneurolysis (Lloyd Neurostat, Spembly Medical, Hampshire, UK), 62% experienced greater than a 50% reduction in pain (deemed a responder) after 1 year and 76% experienced a reduction in VAS pain score of 3 or more after 1 year. The results also showed that 85% of patients who had not undergone spinal surgery were responders compared to just 47% of those who had undergone previous spinal surgery.…”
Section: Treatment Of Lumbar Facet Joint Painmentioning
confidence: 99%
“…Another study [92] demonstrated that of the 50 patients who underwent cryoneurolysis (Lloyd Neurostat, Spembly Medical, Hampshire, UK), 62% experienced greater than a 50% reduction in pain (deemed a responder) after 1 year and 76% experienced a reduction in VAS pain score of 3 or more after 1 year. The results also showed that 85% of patients who had not undergone spinal surgery were responders compared to just 47% of those who had undergone previous spinal surgery.…”
Section: Treatment Of Lumbar Facet Joint Painmentioning
confidence: 99%
“…Soll der R. medialis denerviert werden, müssen die benachbarten Segmentversorgungen in die Denervation einbezogen werden. Gute Resultate in der Literatur werden bei 85-95% der behandelten Patienten, richtige Indikation vorausgesetzt, berichtet [2,50].…”
Section: Kryotherapie Der Facettengelenkeunclassified
“…RF facet denervation was introduced in clinical practice in the early 1970s, and kryorhizotomy was tried in 2003 for the treatment of LFS [3]. Subsequently, highly variable success rates were demonstrated with beneficial outcomes in 11 to 99% of the cases reported in different series [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, highly variable success rates were demonstrated with beneficial outcomes in 11 to 99% of the cases reported in different series [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%